SYNCHRONIZATION OF HIGH-DIMENSIONAL CHAOS GENERATORS BY OBSERVER DESIGN - GIUSEPPE GRASSI; Saverio Mascolo (International Journal of Bifurcation and Chaos, 1999)
In this Letter a method for synchronizing hyperchaotic systems described by ordinary differential equations (ODEs) as well as functional differential equations (FDEs) is illustrated. The technique, which exploits the concept of observer from system theory, is at first applied for synchronizing an example of high-order circuit. A remarkable feature is that hyperchaos synchronization is achieved via a scalar signal. Successively, the tool is applied for synchronizing an example of high-dimensional chaos generator, represented by a cell equation in Cellular Neural Networks with delay. Finally, the advantages of the proposed approach are discussed in detail.